Improving the Performance of Pupils in Reading Using Word and Sentence Cards among Basic Four Pupils at Abuakwa R/C Primary, Eastern Region (International Journal of Scientific Research and Management (IJSRM), 2020)
ABSTRACT The purpose of the study was to determine the extent to which the pupils at the Abuakwa R/C Primary School can improve upon their reading ability. It was also to find out whether they developed the interest in studying of the English Language. The target sample of the study was made up of forty – nine (49) pupils that made up a whole class. Also, the target sample of the study was post – test, observation and interview as instruments to collect data. The pre-test was conducted before the intervention to reveal the problem while post-test was administered after the intervention to find out the effectiveness of the intervention. The data was collected following a weekly planned research activity. It was collected for the tabulated and converted into sample percentages. This was used for the analysis and discussions of the research question. In conclusion, the effectiveness of the intervention has really helped to improve upon pupils reading ability. Keywords: observation, interview, intervention, interest, improve